Early notification of public transport arrival using radio link - 222750 Tay, Lip Chuan (Skudai : Universiti Teknologi Malaysia, 2005)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Elektronik)) - Universiti Teknologi Malaysia, 2005